TEKNIK EDITING DISKONTINUITI PADA DRAMA TELEVISI 44V - Andhika, Yuditia Leo; Rahman, Abdul; Krishn, Adi (Seni Media Rekam ISI Surakarta, 2017)
This paper describes the creation of a television drama 44V. This work tells about the journey of a courier forwarder who works on a service offer. This work is packed with sitcoms and there is a social critique of the current situation of Indonesian society. Works created using discontinuity editing techniques. This editing technique is breaking the logic of space and time. Discontinuity editing places more emphasis on ignoring the principles and conventions of continuity editing. In combining several techniques with the discontinuity editing method, an editor is required to be creative aesthetically and skillfully enough to collaborate on such techniques either with transitions, visual effects and so forth.Keywords: 44V, discontinuity, and editing